SILICON NITRIDE FILMS PREPARED BY PLASMA-ENHANCED CHEMICAL VAPOUR DEPOSITION (PECVD) OF SiH//4/NH//3/N//2 MIXTURES: SOME PHYSICAL PROPERTIES. - Ling, C.H. (2014)
Japanese Journal of Applied Physics, Part 1: Regular Papers & Short Notes